METHOD FOR PRODUCING GASOLINE ADDITIVES (Scientific journal of the Fergana State University, 2024)
This study experimentally investigated the simultaneous saccharification and fermentation (SSF) process using pre-treated simple cane with Saccharomyces cerevisiae as a catalyst under isothermal (I) and non-isothermal (NI) conditions. The analysis of the dispersion of NI-OOF results utilized the Fisher parameter through the Statistics 7 software to identify significant differences between experimental data obtained at various temperatures. In non-isothermal experiments, the temperature was linearly increased over 96 hours, and the results were compared with those from the isothermal process involving simultaneous saccharification and fermentation. The ethanol concentration produced during the non-isothermal process with a ramping temperature of 0.130 °C/hour reached 15.8 g/L. In comparison, the final ethanol concentrations for the isothermal process were 11.8 g/L at 32 °C and 13.8 g/L at 39 °C. The findings indicated that non-isothermal SSF should be considered as an option for ethanol production based on lignocellulose. It was shown that higher temperatures are more favorable for the OT material. Additionally, it was determined that a linearly increasing temperature for such material leads to a higher final ethanol yield compared to the best isothermal process. The profitability of bioethanol indicates that the non-isothermal process with simultaneous saccharification and fermentation provides a sufficiently higher yield of bioethanol compared to the isothermal process.